Best practice of green rural tourism: lesson from Sangkan Gunung, Karangasem - I Nyoman Winia; Gede Ginaya; I Gede Mudana; I Putu Krisna Arta Widana (International Journal of Green Tourism Research and Applications, 2019)
The objective of this study was to find out the best practice and the factors influence the best practice of Sangkan Gunung rural tourism operator in Karangasem Regency, Bali. The research method employed was structured observation, documents analysis and in depth interview. The findings reveal that, green initiatives help to cut down the running cost and Sangkan Gunung rural tourism adopts the best practice that suit its operation and environment. The Pilot project in Sangkan Gunung rural tourism proposes to regard sustainability issues in the context of rural tourism product quality, integrating sustainability aspects into a running and well recognized rural tourism quality scheme. Promotion of sustainable rural tourism products goes along